EXPERMENTAL INVESTIGATION OF TEMPERATUREFOR STIR FRICTION WELDING DISTRIBUTION - Qasim M. Doos; Suhair G. Hussein (Journal of Engineering, 2024)
Friction stir welding (FSW) is a solid state joining method for metal and is widely used for